Psychophysiological stress response of novel students in chemical laboratory practices (2023)
The aim of the present study was to analyze the psychophysiological stress response of novel pharmacy and biotechnology students in chemistry laboratory practices. Autonomic stress response was analyzed in 66 students by considering heart rate variability (HRV) values before, during, and after their first laboratory practice, as well as their distress perception before and after this activity. In the laboratory practice, students had to deal with toxic products, sharp objects, or irritating substances while being examined by the teachers. Consistent with a large anticipatory anxiety response at the beginning of the practice, results showed low HRV values, generally related to a typical sympathetic modulation. This sympathetic effect persisted during the entire laboratory practice. Moreover, just after the end of the practice, there was an attenuation of the sympathetic activation and a takeover by the parasympathetic system, as revealed by the increase of HRV parameters. Laboratory practices performed by novel Pharmacy and Biotechnology students did not produce the expected habituation response at psychophysiological level since, in addition to an anticipatory anxiety response observed prior to the laboratory practice, a high sympathetic autonomic activation was observed during the whole practice. In brief, using HRV parameters could be a useful tool to analyze stress responses in students and to help them with new strategies to improve routine evaluation procedures. (PsycInfo Database Record (c) 2023 APA, all rights reserved)